Prognostic Value of Excision Repair Cross-Complementing Gene 1, Dihydropyrimidine Dehydrogenase, and Human Equilibrative Nucleotide Transporter 1 Expression and Their Implications for Adjuvant Treatment in Patients With Ampullary Carcinoma. Issue 6 (August 2015) - Kawabata, Yasunari; Nishi, Takeshi; Kidani, Akihiko; Tajima, Yoshitsugu
Abstract : Objectives: The purpose of this study was to characterize the intratumoral expression profiles of excision repair cross-complementing gene 1 (ERCC1), dihydropyrimidine dehydrogenase (DPD), and human equilibrative nucleotide transporter 1 (hENT1) in ampullary carcinomas (ACs) to evaluate their prognostic values and better tailor adjuvant chemotherapy for individual patients with AC after surgery. Methods: This study included 49 patients with AC who underwent a curative pancreaticoduodenectomy. Various clinicopathological factors, including ERCC1, DPD, and hENT1, were analyzed in relation to postoperative disease recurrence and the patients' survival. Results: The median recurrence-free survival and overall survival were 24.5 months and 32.4 months, respectively. Multivariate Cox regression analysis of recurrence-free survival identified a DPD expression (hazard ratio [HR], 8.18; 95% confidence interval [CI], 2.00–34.8; P = 0.003) and combined ERCC1/DPD expression (HR, 134.8; 95% CI, 11.8–1920; P < 0.001) as independent predictors of disease recurrence. Multivariate Cox regression analysis of overall survival also identified a DPD expression (HR, 8.48; 95% CI, 1.71–46.3; P = 0.008) and combined ERCC1/ DPD expression (HR, 135.6; 95% CI, 11.8–1940; P < 0.001) as independent predictors of survival. Conclusions: The DPD and ERCC1 expression profile could potentially serve as a useful prognostic biomarker and therapeutic target for surgically resected patients with AC.